Amphiphilic alginate as well as preparation method and application thereof
The alkane graft of amphiphilic alginate plays an interface stabilization role in reverse phase suspension polymerization, solving the problem that ordinary alginate cannot be distributed at the water/oil interface, and achieving the high water absorption rate of superwater absorbent and stabilize the reaction, reducing production costs.
Patent Information
- Application Number
- CN202411698156.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-07
AI Technical Summary
In reverse phase suspension polymerization, ordinary alginate cannot be effectively distributed at the interface between water and oil and cannot play an interface stabilization role. Commonly used small-molecular surfactants can easily lead to gel formation and incomplete reaction, which affects super-supported ultrasound Water absorption properties of water absorbents.
Develop amphiphilic alginates, which form alginate alkane grafts by crosslinking with alkyl alcohols or alkyl amines, so that they are hydrophilic and lipophilic, and can be self-assembled and distributed at the interface between the aqueous and oil phases, and To wrap and protect, avoid tight buildup, and promote high water absorption rate of superabsorbents.
The reverse phase suspension polymerization process is achieved smoothly, the gel and slurry entanglement are avoided, the high water absorption rate of superwater absorbents and the formation of powder products are promoted, and the production cost is reduced.
Smart Images

Figure CN119264294A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to an amphiphilic alginate, a preparation method and application thereof. Background Art
[0002] Super absorbent is a kind of polymer material with good water absorption and water retention capacity. It can absorb water hundreds or even thousands of times its own weight, and will not dehydrate or dehydrate a small amount of water under pressure. It has been widely used in medical materials, physiological and sanitary materials, agricultural water retention materials, leak-proof sealing materials and other fields. Among them, polyacrylic acid super absorbent is the type with the largest production volume due to its excellent performance. At present, the preparation methods of polyacrylic acid super absorbent include solution polymerization, reverse emulsion polymerization and reverse suspension polymerization. Among them, the reverse suspension polymerization method has the advantages of controllable reaction temperature, low system viscosity, simple post-treatment, direct acquisition of fine granular products, and fast product water absorption rate, which is very convenient for industrial large-scale production. However, when performing the reverse suspension polymerization process of such materials, a stabilizer must be added to maintain the stability of the system. Commonly used small molecule surfactants including Span series are easy to produce gels, entanglement, destroy the reaction process, cause incomplete reaction, affect the water absorption performance of the material, and at the same time, the gel product is difficult to post-process and the reaction vessel is difficult to clean. Compared with small molecule surfactants, amphiphilic polymers can produce larger and more stable spatial effects at the interface of suspension polymerization droplets due to their large molecular structure, making the reverse suspension polymerization process proceed smoothly. Therefore, it is of great significance to develop low-cost amphiphilic polymer stabilizers.
[0003] Alginate is a natural polymer with a polysaccharide structure from the ocean. It is a low-cost, renewable, and green environmentally friendly material. It has excellent water solubility, gelation, biocompatibility, and biodegradability, and has been widely used in textile, cosmetics, food, and pharmaceutical industries. The polysaccharide structure main chain of alginate and the large number of carboxylate anions it contains can produce spatial effects such as spatial isolation and electrostatic repulsion, which protect and stabilize the reaction droplets in the reverse suspension polymerization system. However, to exert this stabilizing effect, alginate must be distributed at the interface between the reaction droplets (aqueous solution dispersed phase) and the oil continuous phase. Ordinary alginate is only hydrophilic and is only evenly dispersed in the aqueous solution dispersed phase. Since it cannot be effectively distributed at the interface between the water and oil phases, it cannot play an interfacial stabilizing role. Summary of the invention
[0004] In view of the fact that ordinary alginate cannot be effectively distributed at the water / oil two-phase interface, cannot play an interfacial stabilizing role, and the demand for low-cost stabilizers in the process of producing super absorbents by reverse suspension polymerization, the development of amphiphilic alginate is of great significance. The purpose of the present invention is to provide an amphiphilic alginate having both hydrophilic and lipophilic properties, so that it can be self-assembled and distributed at the interface of the water phase and the oil phase, and the polymerization droplets are wrapped and protected in the reverse suspension polymerization of the super absorbent, so that the polymerization reaction proceeds smoothly. In addition, during the temperature rise and dehydration process of the polymerization product in the late stage, with the precipitation and accumulation of the super absorbent particles, the wrapping effect of this amphiphilic alginate can avoid the close accumulation of the super absorbent, which is not only convenient for the super absorbent to form a powder product, but also can form a physical gap between the super absorbent particles, as a capillary channel, which is convenient for the rapid absorption of water and realizes the high water absorption rate of the super absorbent.
[0005] The invention provides an amphiphilic alginate, wherein the amphiphilic alginate is an alkane graft of alginate, and the alkane graft of alginate is cross-linked with alginate and an alkyl alcohol or an alkyl amine via epichlorohydrin as a connecting segment.
[0006] Preferably, the alginate is at least one of sodium alginate, potassium alginate, lithium alginate, oxidized sodium alginate, oxidized potassium alginate and oxidized lithium alginate.
[0007] Preferably, the alkyl alcohol or alkyl amine is a monosubstituted product, the alkyl alcohol is a primary alcohol, and the alkyl amine is a primary amine, and the corresponding carbon number is one or more of 5-24.
[0008] The present invention also provides a method for preparing amphiphilic alginate, comprising the following steps: (1) dissolving alginate in deionized water to obtain an alginate aqueous solution; The alginate is at least one of sodium alginate, potassium alginate, lithium alginate, oxidized sodium alginate, oxidized potassium alginate and oxidized lithium alginate; The mass ratio of the alginate (the mass of the repeating unit) to the alkyl alcohol or alkyl amine is 0.1-100; The mass ratio of alginate to deionized water is 0.0001-0.1; (2) adding alkyl alcohol or alkyl amine, alkali, surfactant, and non-polar organic solvent to the alginate aqueous solution and stirring to form a uniform solution; The alkyl alcohol or alkyl amine is a monosubstituted product, the alkyl alcohol is a primary alcohol, the alkyl amine is a primary amine, the corresponding carbon atoms are one or more of 5-24, and the mass ratio of the alkyl alcohol or alkyl amine to epichlorohydrin is 1-50; The base is at least one of sodium hydroxide, potassium hydroxide and triethylamine, and the amount ratio of the base to epichlorohydrin is 1-3; The surfactant is one or more of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, sodium hexadecylbenzenesulfonate, sodium dodecylbenzenesulfonate, sulfated castor oil, sodium dodecyl sulfate, sodium hexadecyl sulfate and sodium octadecyl sulfate, and the mass ratio of the surfactant to the alginate is 0.001-0.1; The non-polar solvent is one or more of n-hexane, cyclohexane and n-heptane, wherein the volume ratio of the non-polar solvent to the alginate aqueous solution is (1-0.01):1; (3) adding epichlorohydrin to the above solution to carry out a reaction; The reaction temperature is 30-90°C and the reaction time is 0.1-48 hours; (4) pouring into a polar organic solvent to precipitate a solid, and soaking the solid; The polar organic solvent is ethanol and / or methanol, and the volume ratio of the polar organic solvent to the alginate aqueous solution is (10-0.1):1; the soaking time is 0.1-24 hours; (5) filtering the solid, then pouring into a polar organic solvent, soaking, filtering, and vacuum drying; The polar organic solvent is ethanol and / or methanol, and the volume ratio of the polar organic solvent to the alginate aqueous solution is (10-0.1):1; the soaking time is 0.1-24 hours; the vacuum drying temperature is 30-90°C, and the vacuum drying time is 0.1-24 hours.
[0009] The invention also provides an application of amphiphilic alginate in preparing super absorbent by reverse phase suspension polymerization.
[0010] The present invention also provides a method for preparing a super absorbent using the above-mentioned amphiphilic alginate, comprising the following steps: (1) Dissolve the polymerizable monomer in water, add a sodium hydroxide solution dropwise, then add a crosslinking agent and an initiator and stir to dissolve to form a dispersed phase aqueous solution of the reactants; The polymerizable monomers are acrylic acid monomers and other monomers with ethylene structures, and specifically the polymerizable monomers are one or more of methacrylic acid, acrylamide, methacrylamide, itaconic acid and maleic acid; the mass concentration (mass percentage) of the polymerizable monomer aqueous solution is 20-55wt%; the mass molar ratio of the polymerizable monomer to sodium hydroxide is 0.1-1; The crosslinking agent is a monomer containing two or more carbon-carbon double bonds, and specifically the crosslinking agent is one or more of N, N-methylenebisacrylamide, ethylene glycol diacrylate and triallylamine, and the mass ratio of the crosslinking agent to the polymerized monomer is 0.00001-0.01; The initiator is one or more of sodium persulfate, potassium persulfate, ammonium persulfate, etc., and the mass ratio of the initiator to the polymerization monomer is 0.0001-0.01; (2) Add the amphiphilic alginate and dispersant to a non-polar solvent. Under stirring conditions, dropwise add the aqueous solution of the reactant prepared in the first step. Then, under a nitrogen atmosphere, maintain a fixed stirring speed for a period of time, then raise the temperature to a predetermined temperature and react for a predetermined time.
[0011] The mass ratio of the amphiphilic alginate to the polymerized monomer is 0.0002-0.02; The dispersant is a non-ionic small molecule surfactant, specifically including one or more of sorbitan monostearate, sucrose fatty acid ester, sorbitan monooleate, triglycerol monostearate, etc., and the mass ratio of the dispersant to the polymerized monomer is 0.005-0.1; The non-polar solvent is one or a mixed solvent of cyclohexane, n-hexane, and n-heptane, and the ratio of the non-polar solvent to water is 10-1; The reaction temperature is 50-90 degrees, and the reaction time is 2-6 hours; (3) Add surface cross-linking agent and stir for a while.
[0012] The surface crosslinking agent is an organic molecule containing two or more epoxy functional groups, such as one or more of ethylene glycol diglycidyl ether, glycerol tri(1,2-epoxy)propyl ether, polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, etc., and the mass ratio of the amount thereof to the polymerizable monomer is 0.00005-0.05; (4) Dehydrating the mixture for a period of time using a water separator to obtain a super absorbent solid, which is then dried using a forced air system to obtain the final product.
[0013] The invention also provides a super absorbent prepared by the method.
[0014] Specifically, the material design principle of the amphiphilic alginate of the present invention is as follows: The raw material alginate is from the ocean, which is rich in resources, renewable, degradable, and belongs to green environmental protection materials with low cost. From the perspective of molecular structure, alginate has abundant hydroxyl and carboxylate groups, among which hydroxyl groups serve as the connection sites for grafting reactions. Through epoxy ring-opening reaction, alkyl chains can be grafted to form amphiphilic polymers; the carboxylate groups contained can be ionized into carboxylate anions, producing electrostatic repulsion, which can inhibit the adhesion and gelation of super absorbent reaction droplets during the reverse suspension polymerization process, which are not conducive to the polymerization reaction, and play a stabilizing role; in addition, this amphiphilic polymer self-assembles on the surface of super absorbent particles to form lipophilic alkyl chains, which can inhibit the close accumulation of particles during the later dehydration and accumulation process of super absorbent particles, facilitating the formation of powdered products, and also forming a large number of physical gaps as capillary channels for water absorption performance, ensuring the high water absorption rate of super absorbents. Epichlorohydrin is used as a cross-linking agent for grafting reactions, with high reaction activity, mild grafting conditions, simple operation, and convenient large-scale production.
[0015] The beneficial effects of the amphiphilic alginate prepared by the present invention are: 1. The main chain steric hindrance and electrostatic repulsion of amphiphilic alginate play a good role in stabilizing the reaction droplets at the interface of the reaction droplets, which can achieve a smooth and smooth reverse suspension polymerization process of the super absorbent, and effectively avoid the occurrence of gelation, entanglement, and even explosion of the reaction droplets of the absorbent.
[0016] 2. Amphiphilic alginate forms alkyl chains on the surface of the absorbent particles. During the dehydration, solidification and deposition of the absorbent reaction droplets in the late stage of inverse suspension polymerization, it can inhibit the close accumulation of particles and promote the formation of powdered products. At the same time, it also forms physical gaps between the absorbent particles, which is convenient for the capillary water absorption mechanism of the absorbent and achieves a high water absorption rate of the absorbent.
[0017] 3. Alginate, the raw material of amphiphilic alginate, is a marine biomass resource with abundant sources, easy to obtain on a large scale, low cost, and also has the advantages of biocompatibility and degradability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 It is the FTIR spectra of Example 1 (1) before and after sodium alginate grafting (SA).
[0020] Figure 2 It is the morphology picture of the super absorbent powder of Example 3.
[0021] Figure 3 It is the kinetic curve of the water absorption process of the super absorbent powder of Example 3. DETAILED DESCRIPTION
[0022] A method for preparing an amphiphilic alginate comprises the following steps: dissolving alginate, alkyl alcohol or alkyl amine and alkali in water to form an aqueous solution; Adding a surfactant and a non-polar organic solvent into the aqueous solution to form a solution system; Adding epichlorohydrin to the solution system for reaction at a temperature of 30-90° C. for a reaction time of 12-36 hours to obtain a reaction solution; The reaction solution is mixed with a polar solvent, allowed to stand, filtered, and dried; The ratio of the alginate, alkyl alcohol or alkyl amine, base, water, surfactant, non-polar organic solvent, epichlorohydrin, and polar solvent is (1-3 g): (0.1-10 mmol): (0.5-1.5 g): (40-100 mL): (0.02-0.09 g): (1-3 mL): (1-5 mL): (40-100 mL); The alginate is at least one of sodium alginate, potassium alginate, lithium alginate, oxidized sodium alginate, oxidized potassium alginate and oxidized lithium alginate; The alkyl alcohol or alkyl amine is a monosubstituted product, the alkyl alcohol is a primary alcohol, the alkyl amine is a primary amine, and the corresponding carbon number is one or more of 5-24; preferably, the alkyl alcohol is n-dodecanol, n-tridecanol, n-tetradecanol, n-pentadecanol, n-hexadecanol, n-heptadecanol or n-octadecyl alcohol; The base is at least one of sodium hydroxide, potassium hydroxide and triethylamine; The surfactant is one or more of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, sodium hexadecylbenzenesulfonate, sodium dodecylbenzenesulfonate, sulfated castor oil, sodium dodecyl sulfate, sodium hexadecyl sulfate and sodium octadecyl sulfate; The non-polar solvent is one or more of n-hexane, cyclohexane and n-heptane; The polar organic solvent is ethanol and / or methanol.
[0023] In the present preparation method, alginate such as sodium alginate is dissolved in deionized water to form a uniform aqueous solution. Alginate, as a hydrophilic polymer, can be well dissolved by forming hydrogen bonds with water molecules. Alkyl alcohol or alkyl amine, such as n-dodecanol or n-octadecyl alcohol, as a monosubstituted substance, has good solubility in non-polar solvents and has good lipophilic properties, so the alginate graft has both hydrophilic and lipophilic amphiphilic properties. Alkali such as sodium hydroxide plays a neutralizing role in this process, which can enhance the reactivity of epichlorohydrin, making it easier to react with alginate, alkyl alcohol or alkyl amine, thereby forming an alginate graft.
[0024] Furthermore, a surfactant such as hexadecyltrimethylammonium bromide and a non-polar organic solvent such as n-hexane are added to the aqueous solution. The surfactant is added to reduce the surface tension of the solution, promote the dispersion of the non-polar solvent in the aqueous phase, and increase the aqueous phase / oil phase interface; the addition of the non-polar organic solvent promotes the dissolution of the alkyl alcohol or alkyl amine, and combined with the dispersing effect of the surfactant, the chemical reaction between the alginate and the alkyl alcohol or alkyl amine is promoted smoothly.
[0025] Further, epichlorohydrin is added to the above solution system and reacted at a temperature of 30-90°C for 12-36 hours. Epichlorohydrin, as an active epoxy compound, can react with the hydroxyl group in alginate, the hydroxyl group or amino group of alkyl alcohol or alkyl amine to form a chemical bond, thereby forming an alginate graft. This reaction is carried out through a nucleophilic substitution mechanism, and the final product has amphiphilic characteristics.
[0026] After the reaction is completed, the reaction solution is mixed with a polar organic solvent such as ethanol or methanol, and filtered and dried after standing. The addition of polar solvents helps to precipitate the amphiphilic alginates generated by the reaction from the reaction solution because they are insoluble in polar solvents. The standing process allows the generated solids to settle out, which is convenient for the subsequent filtering step. This process ensures the collection of high-purity amphiphilic alginates, and the drying step further removes the solvent.
[0027] A method for preparing a super absorbent using the above-mentioned amphiphilic alginate comprises the following steps: (1) Dissolve the polymerizable monomer in water, add a sodium hydroxide solution dropwise at a temperature of -5°C to 5°C, then add a crosslinking agent and an initiator and stir to dissolve, thereby forming a dispersed phase aqueous solution of the reactants; The polymerizable monomer is one or more of acrylic acid, methacrylic acid, acrylamide, methacrylamide, itaconic acid and maleic acid; The ratio of sodium hydroxide to water in the sodium hydroxide solution is (1-3 g): (2-20 mL), preferably 1 g: (2-4 mL); The cross-linking agent is one or more of N, N-methylenebisacrylamide, ethylene glycol diacrylate and triallylamine; The initiator is one or more of sodium persulfate, potassium persulfate and ammonium persulfate; (2) dissolving the amphiphilic alginate and dispersant in a non-polar solvent, adding dropwise the dispersed phase aqueous solution of the reactant, and stirring the reaction at 50-90° C. for 2-6 hours under an inert gas atmosphere; The dispersant is one or more of sorbitan monostearate, sucrose fatty acid ester, sorbitan monooleate and tripolyglycerol monostearate; The non-polar solvent is one or more of cyclohexane, n-hexane and n-heptane; (3) Add the surface cross-linking agent and stir evenly; specifically, stir for 1-3 hours; The surface crosslinking agent is one or more of ethylene glycol diglycidyl ether, glycerol tri(1,2-epoxy)propyl ether, polypropylene glycol diglycidyl ether and polyethylene glycol diglycidyl ether; (4) Dehydration: Dehydration can be carried out by using a water separator at 100-140℃ for 2-6h; The usage ratio of polymerization monomer, water, sodium hydroxide solution, crosslinking agent, initiator, amphiphilic alginate, dispersant, non-polar solvent and surface crosslinking agent is (3-10g):(1-3mL):(3-8mL):(0.1-1mg):(1-5mg):(0.002-0.02g):(0.05-0.15g):(10-30mL):(10-20mg).
[0028] The following is a detailed introduction to each step in the preparation of super absorbent and the role of the raw materials used: Step 1: Reaction of polymer monomers with sodium hydroxide In this step, a polymerizable monomer such as acrylic acid is dissolved in water, and a sodium hydroxide solution is added dropwise at a low temperature of -5°C to 5°C. Low temperature conditions can avoid excessive temperatures due to heat release during the neutralization reaction to prevent the occurrence of polymerization reactions of the polymerizable monomers. Sodium hydroxide reacts with monomers such as acrylic acid to generate polymerizable monomer salt compounds such as acrylates. This conversion process can increase the degree of ionization of the polymerizable monomers and enhance their hydrophilicity. It is also a necessary functional group for the subsequent water absorption process of the superabsorbent. Next, a crosslinking agent such as N, N-methylenebisacrylamide and an initiator such as sodium persulfate are added. The crosslinking agent contains multiple active sites and can form a chemical crosslinking structure during the polymerization process to form a network structure of the superabsorbent; the initiator decomposes to produce free radicals when heated, which initiates the polymerization reaction of the monomers, and finally forms a network polymer structure containing a crosslinking structure, thereby achieving high water absorption and water retention of the superabsorbent.
[0029] Step 2: The amphiphilic alginate, the dispersant and the dispersed phase of the reactants are dissolved and reacted.
[0030] In this step, the amphiphilic alginate and the dispersant are dissolved in a non-polar solvent such as n-heptane to form a hydrophobic medium. Dispersants such as Span60, as non-ionic surfactants, can reduce the interfacial tension between the non-polar solvent and the aqueous solution to form a more stable water-in-oil (W / O) emulsion structure. At this time, the aqueous solution of the reactants prepared in step 1 is added dropwise to the organic solution of amphiphilic alginate and dispersant. The nitrogen atmosphere is used to exclude oxygen to avoid the adverse effects of oxygen on the polymerization process. Subsequently, the reaction is stirred at 50-90°C for 2-6 hours to allow the polymer chain to grow and gradually form a stable network structure, thereby improving the structural stability and water absorption performance of the superabsorbent.
[0031] Step 3: Adding surface crosslinker At the end of the polymerization reaction, a surface crosslinking agent such as ethylene glycol diglycidyl ether is added and stirred for 1-3 hours to promote uniform distribution. The surface crosslinking agent has multiple epoxy functional groups, which can react with the hydroxyl or carboxyl groups on the polymer chain on the surface of the super absorbent particles to further enhance the crosslinking density on the surface of the super absorbent particles. The surface crosslinking effect can increase the mechanical strength of the super absorbent particles and facilitate the use of the super absorbent to absorb and retain water.
[0032] Step 4: Dehydration and drying In the last step, the reaction system is dehydrated at 100-140°C using a water separator for 2-6 hours to remove water from the absorbent in order to obtain a super absorbent powder with a stable structure and a high water absorption rate. This is an important step in synthesizing super absorbents using inverse suspension polymerization. The added amphiphilic alginate plays a role in encapsulating and stabilizing the super absorbent particles in this step. This not only ensures the effective dehydration of the super absorbent, but also prevents the super absorbent from condensing into large pieces, without the need for complex processing such as cutting into small pieces. Small granular absorbents are a necessary condition for the high water absorption rate of the material, and can meet the needs of rapid water absorption scenarios in practical applications.
[0033] The content of the present invention can be more easily understood by selecting the following detailed description of the preferred implementation method of the present invention and the embodiments included. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a contradiction, the definition in this specification sheet shall prevail. The following embodiments illustrate the present invention in more detail, rather than limiting the present invention to these embodiments. Embodiment 1:
[0034] (1) Dissolve 1.6 g of sodium alginate, 3.3 g of n-octadecyl alcohol, and 0.99 g of sodium hydroxide in 60 mL of deionized water and stir to form a uniform aqueous solution; (2) Add 0.056 g of hexadecyltrimethylammonium bromide and 2 mL of n-hexane to the aqueous solution and stir to form a uniform solution system; (3) Add 2.7 mL of epichlorohydrin to the above solution system, raise the temperature to 50°C, and stir to react for 24 hours; (4) Pour the reaction solution into 60 mL of ethanol, let it stand for 24 h, and allow the solid to settle; (5) Filter the solid, pour it into 60 mL of ethanol, and soak it for 24 hours. Filter to obtain a solid. Filter and dry to obtain a solid product, which is the amphiphilic alginate of the present invention.
[0035] Figure 1 The Fourier transform infrared spectra of sodium alginate (SA) before grafting and amphiphilic sodium alginate Example 1 (1) after grafting are shown in FIG. 1 . Compared with sodium alginate (SA) before grafting, amphiphilic sodium alginate Example 1 (1) after grafting has a higher infrared spectroscopy in the range of 2800-3000 cm -1 The peak intensity in the range is significantly enhanced, corresponding to the stretching vibration of the carbon-hydrogen bond of the alkane, indicating that sodium alginate SA is grafted onto the alkane chain and the grafting reaction is successful. Embodiment 2:
[0036] (1) Dissolve 1.6 g of sodium alginate, 3.0 g of n-dodecanol, and 0.99 g of sodium hydroxide in 60 mL of deionized water and stir to form a uniform aqueous solution; (2) Add 0.056 g of hexadecyltrimethylammonium bromide and 2 mL of n-hexane to the aqueous solution and stir to form a uniform solution system; (3) Add 2.7 mL of epichlorohydrin to the above solution system, raise the temperature to 50°C, and stir to react for 24 hours; (4) Pour the reaction solution into 60 mL of ethanol, let it stand for 12 h, and allow the solid to settle; (5) Filter the solid, pour it into 60 mL of ethanol, and soak it for 12 hours. Filter the solid. Filter and dry to obtain a solid product, which is the amphiphilic alginate of the present invention. Embodiment 3:
[0037] (1) Dissolve 5 g of acrylic acid in 2 mL of deionized water, add dropwise a sodium hydroxide solution prepared by dissolving 1.95 g of sodium hydroxide in 5 mL of deionized water under ice-water bath conditions, then add 0.4 mg of N,N-methylenebisacrylamide and 3 mg of ammonium persulfate, and stir to dissolve to form a reactant aqueous solution; (2) Dissolve 0.01 g of the amphiphilic alginate prepared in Example 1 and 0.1 g of the dispersant Span 60 in 17 mL of n-heptane. Add the aqueous solution of the reactant prepared in the first step dropwise under stirring. Then, stir at 30°C for 0.5 h under a nitrogen atmosphere, raise the temperature to 75°C, and stir for 3 h.
[0038] (3) Add 14.4 mg of ethylene glycol diglycidyl ether and stir for 1.5 h.
[0039] (4) Install a water separator and dehydrate at 125°C for 3 hours to obtain a super absorbent solid. The solid is dried by forced air to obtain the final product super absorbent.
[0040] Figure 2 is a morphology diagram of the super absorbent powder prepared in this example. Figure 2 It can be seen that by adding the amphiphilic sodium alginate prepared by the present invention as an interfacial stabilizer, the microscopic morphology of the super absorbent powder synthesized by one-step reverse phase polymerization maintains a good spherical morphology, indicating that the reverse suspension polymerization process is successfully completed, the particle size of a single sphere is 1-100 μm, and the spheres are bonded to form agglomerates of several hundred μm. This morphology is convenient for the sample filtration process, and also provides a large specific surface area and a large number of water absorption channels between particles, which is convenient for achieving a high water absorption rate of the super absorbent.
[0041] Water absorption performance test: The present invention studies the water absorption performance of the super absorbent white powder prepared in Example 3. Specific steps: weigh 0.1g of the super absorbent white powder prepared in Example 3, put it into 100mL of deionized water, let it stand for a predetermined time, filter out the free water with an 80-mesh mesh sieve, and then weigh the gel mass at different predetermined times (0min, 1min, 3min, 5min, 10min, 20min and 60min), and calculate the liquid absorption rate at different predetermined times according to the following formula: Water absorption rate = mass of sample after absorbing water / mass of dry sample The results are as follows Figure 3 As shown, it can be found that the super absorbent synthesized using the amphiphilic alginate of the present invention can quickly absorb 242 times of water in 1 minute; and 277 times of water in 3 minutes, which is close to the water absorption limit, showing rapid water absorption performance, and can be used for the demand of rapid water absorption in real life.
[0042] The present invention proposes a kind of alginate graft with both hydrophilic and lipophilic properties, which can be effectively distributed at the interface of water / oil phase, and is suitable for the reverse suspension polymerization method of super absorbent. First, the amphiphilic alginate can be self-assembled and distributed at the interface of water phase and oil phase, and the polymerization droplets are wrapped and protected in the reverse suspension polymerization of super absorbent, so that the polymerization reaction is carried out smoothly. Secondly, in the process of heating and dehydration of the product in the late stage of the polymerization reaction, along with the precipitation and accumulation of super absorbent particles, the wrapping effect of the amphiphilic alginate still exists and inhibits the close accumulation of super absorbent. This not only facilitates the formation of powder products by super absorbent, but also promotes the formation of physical gaps between super absorbent particles, which serves as a channel for water to enter, facilitates the rapid absorption of water, and realizes the high water absorption rate of super absorbent.
[0043] Combining the role of this amphiphilic alginate graft in super absorbent synthesis, product collection, and water absorption performance, the needs of super absorbent in actual production can be met.
[0044] The raw material of this invention is alginate polysaccharides, which are abundant, low-cost and inexhaustible. They also have outstanding environmental advantages such as biocompatibility, making them easy to produce on a large scale.
[0045] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. An amphiphilic alginate, characterized in that: The amphiphilic alginate is an alkane graft of alginate, and the alkane graft of alginate is formed by cross-linking alginate and alkyl alcohol or alkyl amine via epichlorohydrin as a connecting segment.
2. The amphiphilic alginate according to claim 1, characterized in that The alginate is at least one of sodium alginate, potassium alginate, lithium alginate, oxidized sodium alginate, oxidized potassium alginate and oxidized lithium alginate.
3. The amphiphilic alginate according to claim 1, characterized in that The alkyl alcohol or alkyl amine is a monosubstituted product, the alkyl alcohol is a primary alcohol, and the alkyl amine is a primary amine, and the corresponding carbon number is one or more of 5-24.
4. The method for preparing the amphiphilic alginate according to any one of claims 1 to 3, characterized in that: The steps include: (1) dissolving alginate in deionized water to obtain an alginate aqueous solution; Adding alkyl alcohol or alkyl amine, alkali, surfactant and non-polar organic solvent to the alginate aqueous solution and stirring to form a uniform solution; (3) adding epichlorohydrin to the above solution to carry out a reaction; The reaction temperature is 30-90°C and the reaction time is 0.1-48 hours; (4) pouring into a polar organic solvent to precipitate a solid, and soaking the solid; (5) Filter the solid, then pour into a polar organic solvent, soak, filter, and vacuum dry.
5. The method for preparing the amphiphilic alginate according to claim 4, characterized in that: In step (1), the alginate is at least one of sodium alginate, potassium alginate, lithium alginate, oxidized sodium alginate, oxidized potassium alginate and oxidized lithium alginate; The mass ratio of the alginate repeating unit to the alkyl alcohol or alkyl amine is 0.1-100; The mass ratio of the alginate to deionized water is 0.0001-0.
1.
6. The method for preparing the amphiphilic alginate according to claim 4, characterized in that: In step (2), the alkyl alcohol or alkyl amine is a monosubstituted product, the alkyl alcohol is a primary alcohol, the alkyl amine is a primary amine, the corresponding carbon number is one or more of 5-24, and the mass ratio of the alkyl alcohol or alkyl amine to epichlorohydrin is 1-50; The base is at least one of sodium hydroxide, potassium hydroxide and triethylamine, and the amount ratio of the base to epichlorohydrin is 1-3; The surfactant is one or more of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, sodium hexadecylbenzenesulfonate, sodium dodecylbenzenesulfonate, sulfated castor oil, sodium dodecyl sulfate, sodium hexadecyl sulfate and sodium octadecyl sulfate, and the mass ratio of the surfactant to the alginate is 0.001-0.1; The non-polar solvent is one or more of n-hexane, cyclohexane and n-heptane, wherein the volume ratio of the non-polar solvent to the alginate aqueous solution is (1-0.01):
1.
7. The method for preparing the amphiphilic alginate according to claim 4, characterized in that: In step (4), the polar organic solvent is ethanol and / or methanol, and the volume ratio of the polar organic solvent to the alginate aqueous solution is (10-0.1):1; the immersion time is 0.1-24 hours; In step (5), the polar organic solvent is ethanol and / or methanol, and the volume ratio of the polar organic solvent to the alginate aqueous solution is (10-0.1):1; the soaking time is 0.1-24 hours; the vacuum drying temperature is 30-90°C, and the vacuum drying time is 0.1-24 hours.
8. Use of the amphiphilic alginate according to any one of claims 1 to 3 in the preparation of super absorbents by inverse suspension polymerization.
9. A method for preparing a super absorbent, characterized in that: The steps include: (1) Dissolve the polymerizable monomer in water, add a sodium hydroxide solution dropwise at low temperature, then add a crosslinking agent and an initiator and stir to dissolve to form a reactant aqueous solution; The mass percentage of the polymerizable monomer aqueous solution is 20-55wt%; the molar ratio of the polymerizable monomer to sodium hydroxide is 0.1-1; The mass ratio of the crosslinking agent to the polymerization monomer is 0.00001-0.01; The mass ratio of the initiator to the polymerization monomer is 0.0001-0.01; (2) adding the amphiphilic alginate and dispersant described in any one of claims 1 to 3 into a non-polar solvent, adding dropwise the aqueous solution of the reactant prepared in the first step under stirring, and then stirring the reaction under a nitrogen atmosphere; The mass ratio of the amphiphilic alginate to the polymerized monomer is 0.0002-0.02; The dispersant is a non-ionic small molecule surfactant, and the mass ratio of the amount to the polymerization monomer is 0.005-0.1; The non-polar solvent is one or a mixed solvent of two or more of cyclohexane, n-hexane and n-heptane, and the ratio of the non-polar solvent to water is 10-1; The reaction temperature is 50-90 degrees, and the reaction time is 2-6 hours; (3) Add surface cross-linking agent and stir; The mass ratio of the surface crosslinking agent to the polymerization monomer is 0.00005-0.05; (4) Dehydration in a water separator to produce a super absorbent.
10. A super absorbent, characterized in that: Prepared by the method of claim 9.